2021
DOI: 10.1002/jlb.3mia0321-150rr
|View full text |Cite
|
Sign up to set email alerts
|

Plasma extracellular vesicles released after severe burn injury modulate macrophage phenotype and function

Abstract: Extracellular vesicles (EVs) have emerged as key regulators of immune function across multiple diseases. Severe burn injury is a devastating trauma with significant immune dysfunction that results in an ∼12% mortality rate due to sepsis‐induced organ failure, pneumonia, and other infections. Severe burn causes a biphasic immune response: an early (0–72 h) hyper‐inflammatory state, with release of damage‐associated molecular pattern molecules, such as high‐mobility group protein 1 (HMGB1), and proinflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…Immunosuppressive (IS) status refers to low immune response. Generally, typical immunosuppressive status includes patients with hematological diseases, tumor, oral immunosuppressive medications, solid-organ transplant, stem cell transplant, or bone marrow transplant, and atypical immunosuppressive status includes patients with diabetes mellitus, liver cirrhosis, and burns ( Mylotte and Tayara, 2000 ; Li et al., 2021 ; Willis et al., 2021 ). Studies revealed that immunosuppression could result from critical surgery as well ( Si et al., 2021 ), and sometimes postoperative patients are susceptible to infections caused by opportunistic pathogens ( Mada et al., 2020 ; Shipman et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressive (IS) status refers to low immune response. Generally, typical immunosuppressive status includes patients with hematological diseases, tumor, oral immunosuppressive medications, solid-organ transplant, stem cell transplant, or bone marrow transplant, and atypical immunosuppressive status includes patients with diabetes mellitus, liver cirrhosis, and burns ( Mylotte and Tayara, 2000 ; Li et al., 2021 ; Willis et al., 2021 ). Studies revealed that immunosuppression could result from critical surgery as well ( Si et al., 2021 ), and sometimes postoperative patients are susceptible to infections caused by opportunistic pathogens ( Mada et al., 2020 ; Shipman et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes, which are the precursors to macrophages and dendritic cells, are the main effector cells against invading bacteria. Accumulating evidence suggests that decreased monocytes, which are very common in burns, sepsis and following major surgeries, may be intimately associated with patient outcomes [23,24]. For example, Osuka et al noted that monocyte count at day 10 was predictive of 30-day mortality in patients with extensive burns [4].…”
Section: Discussionmentioning
confidence: 99%
“…All data were examined in GraphPad Prism Version 9.0 for Windows and analyzed using a one-way analysis of variance (ANOVA) with a Tukey post-test. For NanoString, a negative binomial mixture model, simplified negative binomial model, or loglinear model was used depending on each gene’s mean expression compared to the background threshold, as we described previously [ 71 , 72 ]. Multiple testing correction was performed using the method of Benjamini–Yekutieli.…”
Section: Methodsmentioning
confidence: 99%